An Electrochemical Sensor Based on Ultra-Micro Activated Carbon for the Determination of Puerarin. Issue 2 (1st January 2019) - Sun, Bolu; Li, Dai; Cai, Jinying; Li, Wuyan; Gou, Xiaodan; Gou, Yuqiang; Hu, Fangdi
Abstract : After intensely ultrasonic cracking, activated carbon obtained larger specific surface area in the premise of the high electric conductivity being maintained, which has provided a prerequisite for the construction of highly sensitive electrochemical sensors. An electrochemical sensor for sensitive analysis of puerarin in Radix Puerariae was successfully constructed using the prepared ultra-micro activated carbon in this work. The electrochemical behavior of puerarin on the sensor was investigated by cyclic voltammetry and differential pulse voltammetry. Moreover, the conditions of sensor preparing and puerarin detecting were optimized. Under the optimal conditions, the oxidation peak current increased linearly with the concentration of puerarin in the range of 2.4 × 10 −7 mol L −1 ∼1.54 × 10 −5 mol L −1, and the detection limit was 6.4 × 10 −8 mol L −1 . In addition, the proposed sensor also exhibited good reproducibility, stability and selectivity. With superior performance in sample analysis, the proposed method would not only provide a new way for rapid and sensitive detection of puerarin, but also give a new idea for the application of activated carbon materials in the field of electrochemical sensors.